Evolutionary Histories of Type III Polyketide Synthases in Fungi - Navarro-Muñoz, Jorge Carlos; Collemare, Jérôme (Frontiers in Microbiology, 2020)
Type III polyketide synthases (PKSs) produce secondary metabolites with diverse biological activities, including antimicrobials. While they have been extensively studied in plants and bacteria, only a handful of type III PKSs from fungi has been characterized in the last 15 years. The exploitation of fungal type III PKSs to produce novel bioactive compounds requires understanding the diversity of these enzymes, as well as of their biosynthetic pathways. Here, phylogenetic and reconciliation analyses of 522 type III PKSs from 1,193 fungal genomes revealed complex evolutionary histories with massive gene duplications and losses, explaining their discontinuous distribution in the fungal tree of life. In addition, horizontal gene transfer events from bacteria to fungi and, to a lower extent, between fungi, could be inferred. Ancestral gene duplication events have resulted in the divergence of eight phylogenetic clades. Especially, two clades show ancestral linkage and functional co-evolution between a type III PKS and a reducing PKS genes. Investigation of the occurrence of protein domains in fungal type III PKS predicted gene clusters highlighted the diversity of biosynthetic pathways, likely reflecting a large chemical landscape. Type III PKS genes are most often located next to genes encoding cytochrome P450s, MFS transporters and transcription factors, defining ancestral core gene clusters. This analysis also allowed predicting gene clusters for the characterized fungal type III PKSs and provides working hypotheses for the elucidation of the full biosynthetic pathways. Altogether, our analyses provide the fundamental knowledge to motivate further characterization and exploitation of fungal type III PKS biosynthetic pathways.